Is Learning by Exporting Important? Micro-Dynamic Evidence from Colombia, Mexico, and Morocco - Clerides, S. K.; Lach, S.; Tybout, J. R. (Quarterly Journal of Economics, 1998)
Do firms become more efficient after becoming exporters? Do exporters generate positive externalities for domestically oriented producers? In this paper we tackle these questions by analyzing the causal links between exporting and productivity using plant-level data. We look for evidence that firms' cost processes change after they break into foreign markets. We find that relatively efficient firms become exporters; however, in most industries, firms' costs are not affected by previous exporting activities. So the well-documented positive association between exporting and efficiency is explained by the self-selection of the more efficient firms into the export market. We also find some evidence of positive regional externalities.